The land before time. XI, Invasion of the tinysauruses - Grosvenor, Charles; Ingle, John.; Curzon, Aria Noelle, 1987-; Bennett, Jeff, 1963-; Spam, Aaron; Paulsen, Rob, 1956-; Tavera, Michael; Freudberg, Judy.; Geiss, Tony.; Universal Pictures (Firm); Universal Studios Home Video (Firm) (Universal City, CA : Universal : Distributed by Universal Studios Home Video, 2005)
Littlefoot spoils Nibbling Day and blames it on a herd of tiny mussauruses. The adults get angry and set off an avalanche that opens a tunnel and allows two velociraptors into the valley. Everyone must work together to chase them off.
Based on the characters created by Judy Freudberg and Tony Geiss.
Special features: 'The land before time' music video; 'The land before time' sing-along songs from all 11 'The land before time' adventures.
Animators, Eagle Cheng ... [et al.] ; art director, Flammarion Ferreira ; editor, Jay Bixsen ; music, Michael Tavera.
Voices: John Ingle, Aria Noelle Curzon, Jeff Bennett, Aaron Spam, Rob Paulsen, Anndi McAfee, Kenneth Mass, Miriam Flynn, Cree Summer-Francks, Michael Clarke Duncan, Camryn Manheim.
MPAA rating: G.
DVD, region 1, full screen (1.33:1) presentation; Dolby Digital 5.1 surround.
Keywords: Littlefoot (Fictitious character : Freudberg) -- Juvenile drama; Mussaurus -- Juvenile drama; Dinosaurs -- Juvenile drama; Flowering trees -- Juvenile drama; Feature films; Films for the hearing impaired; Children's -- Feature